Accelerating Hydropower Investment for Economic Growth in North Tapanuli, Indonesia - Jonner Julifer; Charloq Nababan; Erika Revida (TALENTA Publisher, Universitas Sumatera Utara, 2025)
TThis study aims to analyze the influence of infrastructure availability, human resources, tax incentives, political stability, and the investment climate on accelerating investment in the renewable energy sector—specifically hydropower—and regional economic development in North Tapanuli Regency. The study involved a saturated sample of 308 respondents: hydropower investors from 23 project sites, government officials, and local communities. Data analysis was conducted using both descriptive and quantitative methods. The findings reveal that infrastructure availability, human resources, tax incentives, political stability, and the investment climate all significantly influence the acceleration of investment in the renewable energy sector (hydropower) and regional economic development, both partially and simultaneously, in North Tapanuli. Human resources and political stability have the most substantial impact on these variables. High-quality human resources contribute to productivity and innovation, attracting investors, while political stability creates an optimal environment for investment—both critical for regional economic growth. This research serves as a vital foundation for creating a conducive investment climate, accelerating regional economic development, and fostering sustainable opportunities for future economic growth.